Political Consultant Style 2024 Regional Election Campaign Monitoring: Institutional Analysis and Governance of Bawaslu Badung - I Putu Ari Nugraha; AAN Oka Suryadinatha Gorda (CV. RADJA PUBLIKA, 2026)
This study examines the dual role of the Badung Regency Election Supervisory Agency (Bawaslu) in overseeing the 2024 regional election (Pilkada) campaign, focusing on its shift from a purely enforcement-oriented approach toward a consultative-preventive supervisory style. Using a qualitative descriptive-explanatory design, data were collected through in-depth interviews, observation, and document analysis, and analyzed using an interactive model supported by source and technique triangulation. The findings reveal that campaign oversight in Badung operates through regulatory clarification, corrective guidance on activity design, rapid communication channels, and confirmation mechanisms prior to formal findings. This consultative-preventive mode enhances compliance and reduces administrative friction, contributing to greater preventive effectiveness. However, it simultaneously generates governance risks related to accountability and neutrality, particularly when consultation boundaries are not clearly standardized and consultation processes lack adequate documentation trails. The study proposes a regulatory political-consultant style model to conceptualize this adaptive supervisory practice—characterized by rule-based consultation, real-time coordination infrastructure, and discretion bounded by procedural safeguards. The article contributes to public administration and electoral governance studies by highlighting the trade-off between preventive effectiveness and legitimacy risks, and by emphasizing the need for institutional safeguards such as standardized consultation boundaries, equal access mechanisms, and auditable documentation systems.